30-Gb/s Optical Link Combining Heterogeneously Integrated III–V/Si Photonics With 32-nm CMOS Circuits - Dupuis, Nicolas (2015)
https://www.scopus.com/inward/record.url?eid=2-s2.0-84923347115&partnerID=40&md5=5880e003b3aaac1af96bfc0568a8fa98